2016
DOI: 10.18632/oncotarget.10011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of small biopsy specimens and surgical specimens for the detection of EGFR mutations and EML4-ALK in non-small-cell lung cancer

Abstract: Epidermal growth factor receptor (EGFR) mutations and anaplastic lymphoma kinase (ALK) fusion genes represent novel oncogenes that are associated with non–small-cell lung cancers (NSCLC). The feasibility of detecting EGFR mutations and ALK fusion genes in small biopsy specimens or surgical specimens was determined. Of the 721 NSCLC patients, a total of 305 cases were positive for EGFR mutations (42.3%). The rate of EGFR mutations in women was significantly higher than that in men. Histologically, the EGFR muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The echinoderm microtubule-associated protein-like (EML) 4–ALK-positive rate depends on tissue size and is higher in surgical as compared to small biopsy specimens [ 8 ]. In our study, the prevalence of ALK rearrangement in patients with Sq-LC was 1.36%; although all of the cases were diagnosed using small biopsy specimens, this rate was consistent with previous reports [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The echinoderm microtubule-associated protein-like (EML) 4–ALK-positive rate depends on tissue size and is higher in surgical as compared to small biopsy specimens [ 8 ]. In our study, the prevalence of ALK rearrangement in patients with Sq-LC was 1.36%; although all of the cases were diagnosed using small biopsy specimens, this rate was consistent with previous reports [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, our data demonstrate significant intra-tumoral heterogeneity in PACC. Furthermore, classic NSCLC driver mutations [29][30][31][32][33] do not drive tumor development in this subset of lung carcinoma.…”
Section: Clonal Diversitymentioning
confidence: 99%
“…Previous studies have demonstrated that EGFR , a well-known oncogenic driver, contributes to the initiation and progression of lung cancer [ 23 , 24 , 25 ]. A subset of this investigation aimed to confirm whether there is a direct association between SNCA and the EGFR signaling pathway.…”
Section: Resultsmentioning
confidence: 99%